2001
DOI: 10.1021/bi011551k
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Hybrid Backbone Methylphosphonate DNA Heteroduplexes:  Effect of R and S Stereochemistry,

Abstract: Methyl phosphonate oligonucleotides have been used as antisense and antigene agents. Substitution of a methyl group for oxygen in the phosphate ester backbone introduces a new chiral center. Significant differences in physical properties and hybridization abilities are observed between the R(p) and S(p) diastereomers. Chirally pure methylphosphonate deoxyribooligonucleotides were synthesized, and the solution structures of duplexes formed between a single strand heptanucleotide methylphosphonate, d(Cp(Me)Cp(Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…The molecular dynamics results indicate that the overall B conformation of the double helix remains mostly intact, but at the price of a noticeable bending in the helical axis primarily caused by the propagation of this structural distortion along the phosphodiester backbone and base-sugar network. Importantly, in contrast to, for example, methylphosphonate linkages, [28] the disposition of the dioxaphosphorinane linker on the surface of the duplex is not expected to induce significant steric hindrance differences. Indeed, the two modified duplexes position the ethylene bridge of the linker away from the major and minor grooves and directly toward the solvent (D, Figure 3).…”
mentioning
confidence: 99%
“…The molecular dynamics results indicate that the overall B conformation of the double helix remains mostly intact, but at the price of a noticeable bending in the helical axis primarily caused by the propagation of this structural distortion along the phosphodiester backbone and base-sugar network. Importantly, in contrast to, for example, methylphosphonate linkages, [28] the disposition of the dioxaphosphorinane linker on the surface of the duplex is not expected to induce significant steric hindrance differences. Indeed, the two modified duplexes position the ethylene bridge of the linker away from the major and minor grooves and directly toward the solvent (D, Figure 3).…”
mentioning
confidence: 99%
“…[7] The binding affinity order, Sp borano > Rp borano, was contrary to that observed for methylphosphonate substitution, where the Rp diastereomers always formed more stable complexes with the complementary DNA than their Sp counterparts. [8,9] For the phosphorothioate modification, the situation is more complicated-the Rp diastereomers could form DNA duplexes that were more stable, less stable, or with the same stability compared to the Sp analogues. [4,10 -13] A recent thermodynamic study with DNA duplexes containing stereoregular all-Rp, all-Sp, and nonstereoregular ''mix'' phosphorothioate ODNs of different sequences concluded that the relative stability depended on the sequence rather than the phosphorus configuration.…”
Section: Resultsmentioning
confidence: 99%
“…They are normally used as a racemic mixture without separating into isomers [8]. The properties of these diastereomers differ dramati cally [9] and this can be a factor determining the effi cacy of interactions with nucleic acids, such as the for mation of complementary complexes and other more complicated structures [10].…”
Section: Introductionmentioning
confidence: 99%